IMPLEMENTATION OF THE DECISION OF THE 416 SUPREME COURT OF THE REPUBLIC OF INDONESIA ON HEIR GRANTS - Widjatmiko, Kusuma Febry Puspitasari; Yunanto (Awang Long Law Review, 2024)
The decision of the Supreme Court of the Republic of Indonesia 225K/SIP/1960 discusses the implications of heir grants in the context of Indonesian law. This ruling may outline the legal considerations and interpretations given by the Supreme Court to cases relating to heir grants in 1960. However, because I do not have direct access to the contents of the ruling. In a general context, Supreme Court decisions often serve as an important guide for legal practitioners in understanding and applying law in Indonesia.